Assessment and case formulation in counselling and psychotheraphy - Rijn, Biljana van (London : Sage Publications Ltd, 2015)
This is a thorough and well-structured piece of work, which brings in the recent work of excellent authorities such as Barbara Ingram. It is well arranged, with many examples and case vignettes, which bring the material to life in an engaging way. I enjoyed reading it, and would recommend it unreservedly.' John Rowan, humanistic therapist, private practice 'This is a must-read book for students on courses in counselling, psychotherapy, clinical psychology and psychiatry.' Heather Fowlie, Head of the Transactional Analysis Department, Metanoia Institute, London Conducting a competent assessment and case formulation can be a daunting task for trainee therapists engaging in clinical assessment for the first time. This book is designed to help, by unpicking the many aspects involved in assessment and case formulation across ..
Introduction -- What is assessment? -- Assessment structure and skills -- Case formulation -- Diagnosis -- Risk assessment -- Impact of culture and issues of difference -- Ethical considerations --Concluding remarks
Includes bibliographic references and index.
Keywords: COUNSELLING METHODS